Implementation of Compensation for Workers Ending Contract Early: Labor Law Perspectives - Romadhoni, Moh. Risqi Fadjar; Wardoyo, Yohana Puspitasari; Nuryasinta, Radhityas Kharisma (Indonesia Law Reform Journal, 2024)
According to public law, employers are required by statute to pay compensation to employees whose work period has ended or whose completed work has resulted in the termination of their employment relationship. This is specifically related to the implementation of paying compensation to workers with specified time agreement. But what about the employees whose jobs expire before the terms of the employment contract? What are the rights of employees as they relate to labor law which is applied in accordance with both public and private law?. The sociological juridical (empirical) method was employed in this study to gain legal information experimentally. The data were collected through interviews, literature studies, target object observation, and online websites. This study provided multiple findings. First, the agreement was implemented while adhering to the construction mandated by statutory laws and maintaining compliance with existing provisions during its implementation. Second, when considering the factor leading to the termination of the labor agreement prior to its expiration, it could be observed that this incidence was caused by two variables: the employer factor and the employee component. Third, if a worker's work period ended before the work agreement due date, didn’t receive compensation money unless their death caused the work agreement to terminate. Similarly, if a worker's work period ended or the work was completed, they didn’t receive compensation money because the payment was provided during the employment agreement's implementation. It is intended that recommendations derived from this study will consider different viewpoints when putting the agreement into practice. In addition, it is expected of the parties to always work toward a cordial and professional working relationship and to heed any signals sent by the government. Abstrak Dalam pelaksanaan pemberian uang kompensasi kepada pekerja PKWT secara hukum publik bahwa peraturan perundang-undangan mewajibkan pengusaha untuk memberikan uang kompensasi kepada pekerja yang telah habis masa kerjanya atau telah selesainya pekerjaan yang dikerjakan sehingga menyebabkan berakhirnya hubungan kerjaa diantara keduanya. Namun, bagaimana dengan pekerja yang berakhir masa kerjanya sebelum perjanjian kerja berakhir. Bagaimana hak-hak nya pekerja itu jika dilihat dari kacamata hukum ketanagakerjaan yang keberlakuannya menganut dua bentuk hukum yaitu privat dan publik. Adapun metode yang digunakan dalam penelitian ini adalah metode yuridis sosiologis (empiris) yaitu memperoleh pengetahuan hukum secara empiris dengan teknik pengumpulan data melalui observasi pada objek yang dituju, wawancara, studi kepustakaan, dan juga website internet. Dalam penelitian ini menghasilkan beberapa kesimpulan Pertama, bahwa pelaksanaan perjanjian yang terjadi dibuat dengan tetap mengikuti kontruksi yang diperintahkan oleh peraturan perundang-undangan serta dalam pelaksanannya tetap sesuai denagan ketentuan yang ada. Kedua, bila dilihat dari aspek faktor penyebab berakhirnya perjanjian kerja sebelum perjanjian kerja itu berakhir disebabkan oleh dua faktor yaitu dari faktor pekerja itu sendiri dan dari faktor pengusaha yang menyebabkan kejadian ini terjadi. Ketiga, pekerja yang berakhir masa kerjanya sebelum perjanjian kerja berakhir tidak mendapatkan uang kompensasi kecuali perjanjian kerja tersebut berakhir disebabkan oleh pekerja meninggal dunia, dalam hal pekerja yang telah habis masa kerjanya atau telah selesainya pekerjaan yang dikerjakan maka uang kompensasi tersebut juga tidak diterima dikarenakan uang kompensasi tersebut tidak diberikan di akhir melainkan pada saat berjalannya perjanjian kerja. Saran dari penelitian ini diharapkan dalam pelaksanaan perjanjian memperhatikan berbagai perspektif. Selanjutnya para pihak diharapkan selalu mengupayakan hubungan kerja yang baik dan professional serta memperhatikan rambu-rambu yang diberikan oleh pemerintah.